A novel approach: enhancing marigold (Tagetes erecta L.) genetic transformation through seed priming technology - Huang, Wang-Qi; Meng, Chao; Zhang, Lu; Xu, Feng; Yang, Xiu-Mei; Zhang, Li-Fang; Jiang, Ya-Lian; Shi, Rui-Xue; Zhao, A-Xiang; Zhang, Yi-Ping; Ali, Niaz; Chen, Xiu-Hua (Frontiers in Plant Science, 2024)
This research presents an innovative genetic transformation protocol for marigolds (Tagetes erecta L.), a species of great significance in floriculture, impacting both yield and quality. The study introduces seed priming technology as a novel approach and evaluates its effect on the germination rate. The results indicate that the germination rates of pigmented marigold seeds were not significantly affected by Agrobacterium immersion under optimal conditions, although variations were observed in genotypes and treatment parameters. Optimal germination was observed at an optical density (OD600 nm) of 1.3 with a vacuum infiltration time of 10 min. The transgenic plants were confirmed through Basta herbicide resistance, Green florescent protein (GFP) fluorescence screening, and polymerase chain reaction (PCR) detection of the GFP gene. After the treatment, the morphological assessments showed genotype-dependent variations in plant height and fresh weight, while the biochemical analysis revealed significant variations in malondialdehyde (MDA) levels, peroxidase (POD), superoxide dismutase (SOD), and root activities. Additionally, the study examined the efficacy of various scarification techniques on seed survival rate, and seed coat removal was found to be the most effective method for marigold transformation. These findings provide a robust foundation for optimizing genetic transformation methods to enhance marigold crop resilience and quality within the floricultural sector.Materials and Methods